The King-Devick test of rapid number naming for concussion detection: meta-analysis and systematic review of the literature - Kristin M Galetta; Mengling Liu; Danielle F Leong; Rachel E Ventura; Steven L Galetta; Laura J Balcer (Concussion)
Background: Vision encompasses a large component of the brain's pathways, yet is not represented in current sideline testing. Objectives: We performed a meta-analysis of published data for a vision-based test of rapid number naming (King-Devick [K-D] test). Studies & methods: Pooled and meta-analysis of 15 studies estimated preseason baseline K-D scores and sensitivity/specificity for identifying concussed versus nonconcussed control athletes. Result: Baseline K-D (n = 1419) showed a weighted estimate of 43.8 s (95% CI: 40.2, 47.5; I2 = 0.0%; p=0.85 – indicating very little heterogeneity). Sensitivity was 86% (96/112 concussed athletes had K-D worsening; 95% CI: 78%, 92%); specificity was 90% (181/202 controls had no worsening; 95% CI: 85%, 93%). Conclusion: Rapid number naming adds to sideline assessment and contributes a critical dimension of vision to sports-related concussion testing.